2015
DOI: 10.6061/clinics/2015(06)06
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection of pilon fractures

Abstract: OBJECTIVES:Pilon fracture is a complex injury that is often associated with severe soft tissue damage and high rates of surgical site infection. The goal of this study was to analyze and identify independent risk factors for surgical site infection among patients undergoing surgical fixation of a pilon fracture.METHODS:The medical records of all pilon fracture patients who underwent surgical fixation from January 2010 to October 2012 were reviewed to identify those who developed a surgical site infection. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 16 publications
3
27
1
2
Order By: Relevance
“…Studies have shown that the postoperative infection rate of patients with fractures with diabetes reaches 10%–60%. In previous studies, a long operation time indicated a slow healing of the surgical area and an increase in the infection rate. This result is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have shown that the postoperative infection rate of patients with fractures with diabetes reaches 10%–60%. In previous studies, a long operation time indicated a slow healing of the surgical area and an increase in the infection rate. This result is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding infection, Ren et al reported that the risk factors for infection are postoperative glucose concentration >125 mg/dl and a surgical duration >150 min. 26 In our study, we did not analyze these parameters. No variables analyzed in the study were associated with an increased risk of infection; however, infection was logically associated with fair and poor results (AOFAS).…”
Section: Discussionmentioning
confidence: 91%
“…No Brasil, a ISC ocupa a terceira posição entre todas as infecções presentes em serviços de saúde e abrange de 14 a 16% das infecções em pacientes hospitalizados, sendo que 93% dessas são graves, chegando a invadir órgãos ou espaços acessados durante o procedimento cirúrgico, tendo assim uma taxa de incidência de 11% 3 . As estimativas das ISC apresentam uma incidência de 2,3%, e dependem do tipo de vigilância realizada, das particularidades do hospital, do paciente e do procedimento cirúrgico 7 .…”
Section: Introductionunclassified